The need for palliative and support care services for heart failure patients in the community. (25th August 2020) - Ganz, Freda DeKeyser; Roeh, Keshet; Eid, Muhammad; Hasin, Tal; Harush, Chen; Gotsman, Israel
Abstract: Background: Palliative care is a care option considered appropriate for those with heart failure, but is uncommon partially due to a lack of timely identification of those needing palliative care. A standard mechanism that triggers which heart failure patients should receive palliative care is not available. The Gold Standards Framework (GSF) identifies those needing palliative care but has not been investigated with heart failure patients. Objectives: To describe palliative care provided in the community and determine whether the GSF can identify heart failure patients in need of palliative care. Methods: Descriptive study. A total of 252 heart failure patients in the community completed a demographic characteristics questionnaire, the Edmonton symptom assessment scale-revised and the Minnesota living with heart failure questionnaire. Clinical data were collected from the medical chart and the primary physician completed the GSF prognostic indicator guidance. Results: Participants had a mean age of 76.9 years (standard deviation 10.9), most at New York Heart Association level III ( n = 152, 60%). Fewer than half received pain medications ( n = 76, 30%), anxiolytics ( n = 35, 14%), antidepressants ( n = 64, 25%) or sleep medications ( n = 65, 26%). Eight patients spoke with a psychologist or psychologist (3%). One had an advanced directive and 16 (6%) had a record of discussions with their family caregivers. Three (1%) had end-of-life discussions with their healthcare providers. Most healthcare providers responded 'no' to the 'surprise question' ( n = 160, 63%). Sensitivity and specificity of the gold standards framework was poor. Conclusions: Few community dwelling heart failure patients received most aspects of palliative care. The gold standards framework was not a good indicator of those who should receive palliative care.